Through a lens sharply [FluidFocus lens]. - Hendriks, B. (IEEE spectrum)
Philips Research Laboratories has developed the FluidFocus lens that is ideal not only for camera phones but also in products whose design constraints demand a tiny but capable optical system. Like the lens of the human eye, the FluidFocus lens varies its focus by changing shape rather than by changing the relative positions of multiple lenses. The lens uses electrostatic forces to alter the shape of a drop of slightly salty water inside a glass cylinder 3 mm in diameter and 2.2 mm long. One end of the cylinder points toward the image plane while the other is directed at the subject being imaged. The cylinder containing the water drop is filled with oil. Around the inside walls of the cylinder is a water-repellent Teflon-like coating, and behind this coating is an electrode. Basically, the water and the oil makes up the lens, and the shape of the interface between the two determines its focal length. The optical power of the lens that forms at the surface between the oil and the water depends on the curvature of the meniscus and the difference between the refractive indices of the oil and water.